The Influence of Employee Perception and Satisfaction on Remuneration System in Rumah Sakit Islam Klaten and Its Impact on Employee Performance - Hartati, Nuraeni; Hidayah, Nur (RA Journal of Applied Research, 2019)
Background: Several health professions and different educational background become a challenge for human resource management in RS. Islam Klaten. In the hospital; doctors, nurses, and staff have their rights to get appropriate salary based on remuneration system. Some of the challenges are the emergence of many questions and complaints about remuneration. The purpose of this research is to understand the influence of employee perception on their satisfaction and performance when remuneration system has been implemented in RS. Islam Klaten. Subjects and Method: This study was a quantitative research. The subject of this research is all of the employers in RS. Islam Klaten, and take a random sample of 100 people. The data was analyzed by using Partial least square regression to understand the influence and relationship between variables and each indicator. Results: The first hypothesis test results; employee perception influences employee satisfaction in the remuneration system in RS. Islam Klaten, with statistical value 31,781 > t table 1,985. The second hypothesis test results; employee perception of remuneration system influences performance of hospital employees, with statistical value 2.011> t table 1.985. The third hypothesis test results; employee satisfaction of remuneration influences employee performance at the hospital, with statistical t value of 9,095> t table of 1,985. Conclusion: (1) Employee perception influences employee satisfaction of the remuneration system in RS. Islam Klaten. (2) Employee perception of remuneration in RS. Islam Klaten influences employee performance. (3) Employee satisfaction of remuneration in RS. Islam Klaten influences employee performance.